28 Feeding and growth in patients with a ventricular assisted device (VAD): a single-centre retrospective chart review. (23rd February 2023) - Rothman, Brittany; Kidd, Catherine; Morris, Alisa; O'Connor, Graeme
Abstract : Background & Aim: Paediatric cardiomyopathy causes heart failure which may require transplantation; 30–50% of patients listed for transplant require a bridge strategy such as a VAD. Whilst awaiting transplant. VAD patients have a significant mortality risk partly due to adverse events and worsening heart failure symptoms. This review assesses feeding practices for VAD patients within a UK paediatric hospital. Methods: A single-centre chart review for seventeen patients admitted for VAD-implantation between May 2019-April 2022. Data included: anthropometrics, feed type, feeding routes at 6-time points; VAD-implantation, months 2, 4, 6, 9 and immediately pre-transplant. Results: The mean age of VAD-implantation was 4.5 years (±3.1SD). Median time to transplant was 215 days (interquartile range 83, 272). Weight-for-age z-score (WAZ) improved from -1.62 at VAD-implantation (SD±0.83) to -0.71 at transplant (SD±1.08) (p=0.001). Commencing enteral (EN) or parenteral nutrition (PN) post VAD-implantation takes mean time of 2 days (±SD1.18). From VAD-implantation to transplant, PN usage decreased from 41% to 21%; whole protein EN increased from 18% to 29%; partially hydrolysed EN increased from 29% to 50% and amino acid EN decreased from 12% to 0%. Oral intake contributed to nutritional intake for 33% of patients at months 2 and 4, 11% at 6 months and 50% at 9 months. Gastric EN contributed to nutritional intake at 2 months for 60%, 4 months for 50%, 6 months for 56% and 9 months for 67% of patients. Post-pyloric EN contributed to intake in 33% at months 2, 6 and 9 and peaked at 50% at 4 months. No patients were exclusively orally fed. Conclusion: Whilst awaiting transplant, growth improved post VAD-implantation. Feeding routes and types change throughout the VAD course and oral intake is poor with most patients relying on EN. Gastric feeding using hydrolysed formula is the best tolerated option however each patient's journey may differ.